The competition load and sports performance characteristics of elite women`s 3x3 basketball team - LI, D.; WANG, L. (29th Annual Congress of the European College of Sport Science, 2-5 July 2024, Book of Abstracts, 2024)
INTRODUCTION: The 3x3 basketball is an emerging Olympic sport, but there are relevant few sport science and sport performance research on it. This study aim to analyze the game load and performance characteristics of the Chinese womens 3x3 basketball team in 7 matches of the "2019 3x3 Womans Series (3WS)" and 15 matches of the" 2021Olympic Test Matches (OTM)" in Shanghai. METHODS: This study subjects consisted 9 athletes from the Chinese womens 3x3 basketball team(5 guards and 4 centers; average age: 24.1±3.8 years; average height: 180.4±8.8cm; average weight: 78.2±10.9kg). We used the Global Positioning System(GPS) "CATAPULT"(Catapult Group International Ltd,Australia) and "Polar team pro" (Finland, Polar Electro Oy) sensors to collect and analyze internal and external loads. The Lactate Scout (Germany, Senslab GmbH) was used to test blood lactate (mmol.L-¹) to analyze the internal load stress. The significance of differences with * indicating PP<0.05 and ** indicating P<0.01.^ RESULTS: 1)The 3WS averaged duration time was 1754"±41", match density was 53%, the OTM averaged duration time was 1634"±342", and match density was 59%. 2)The 3WS Playload™ and Playload™min were measured at 132.86±18.36a.u, 7.43±0.59a.u**?. The OTM Playload™ and Playload™min were measured at 120.53±25.31a.u**?, 7.19±0.48a.u**?. 3)The 3WS explosive movements was 27±7.46times**?, the OTM explosive movements was 23±9.1times**?. 4)The 3WS average movement changes was 1080±163 times(excluding jumping). Among acceleration:139.5±12.5; deceleration:138±28; changes of direction(COD)-Left: 390±105; COD-right: 354.5±116.5; the number of COD-left and COD-right was almost 2.8 times higher than the number of acceleration and deceleration. 5)The OTM maximum HR 185±14.5bpm, average HR 155±12bpm. The distribution of zones follows: Zone-1: 15.4%,Zone-2:12%,Zone-3: 22.6%, Zone-4: 43.4%, Zone-5: 13.4%. The 3WS maximum HR 200±25bpm**, average HR 168±19bpm**. The distribution of zones follows: Zone-1: 0%**, Zone-2: 8.0%**, Zone-3:17.5%**, Zone-4:29%**, Zone-5:47.5**. 6)The 3WS blood lactate were measured at 6.97±2.8 mmol·L-1 after 2 minutes, and 4.84±1.8mmol·L-1 after 10 minutes. The OTM blood lactate were measured at 6.86±1.05 mmol·L-1 after 2 minutes, and 4.10±0.65 mmol·L-1 after10 minutes. CONCLUSION: In elite Womens 3x3 basketball, the Playload™min has significant increased. The main factors contributing to the increase of explosive movements and acceleration, deceleration, COD-left and COD-right(>3.5m/s). The 3x3 basketball not only is the proportion of anaerobic and glycolytic energy systems significantly higher than 5x5 basketball, but aerobic recovery capacity is also crucial. It requires higher levels of power endurance, and speed agility from players. If players participate in both 3x3 and 5x5 basketball games simultaneously, there is a higher risk of injury, so caution should be exercised.